2005
DOI: 10.1007/s10072-005-0468-8
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric disorders and depression in multiple sclerosis outpatients: impact of disability and interferon beta therapy

Abstract: Associations between psychopathology and gender, duration of MS, disability and therapy with beta-interferons were studied in multiple sclerosis (MS) outpatients. A controlled descriptive epidemiological study was carried out in two Italian outpatient MS centres on 50 outpatients with clinically definite relapsing-remitting MS presenting for regular follow-up and 50 healthy controls matched for sex, age and educational level. Subjects were assessed with the Structured Clinical Interview for DSM-IV (SCID I), th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
61
4
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(80 citation statements)
references
References 0 publications
11
61
4
4
Order By: Relevance
“…Several studies using self-report scales of anxiety symptoms have found a point prevalence of clinically significant anxiety ranging from 25-41%. [38,[60][61] Only two studies have used structured clinical interviews to evaluate formal diagnoses of anxiety disorders, and both of these found lifetime prevalence rates of 36% [10,62], which is much higher than the 25% lifetime rate of anxiety disorders in the general population reported in the National Comorbidity Survey. [63] Generalized anxiety disorder appears to be the most common anxiety disorder among persons with MS, with 18.6% of patients meeting criteria for this disorder.…”
Section: Anxiety Disorders In Msmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies using self-report scales of anxiety symptoms have found a point prevalence of clinically significant anxiety ranging from 25-41%. [38,[60][61] Only two studies have used structured clinical interviews to evaluate formal diagnoses of anxiety disorders, and both of these found lifetime prevalence rates of 36% [10,62], which is much higher than the 25% lifetime rate of anxiety disorders in the general population reported in the National Comorbidity Survey. [63] Generalized anxiety disorder appears to be the most common anxiety disorder among persons with MS, with 18.6% of patients meeting criteria for this disorder.…”
Section: Anxiety Disorders In Msmentioning
confidence: 99%
“…[63] Generalized anxiety disorder appears to be the most common anxiety disorder among persons with MS, with 18.6% of patients meeting criteria for this disorder. [10,62] Panic disorder and obsessive compulsive disorder may also be much more common among MS patients than among the general population. MS patients with anxiety disorders were more likely to be female, and to have a lifetime diagnosis of major depressive disorder or alcohol abuse.…”
Section: Anxiety Disorders In Msmentioning
confidence: 99%
See 1 more Smart Citation
“…According to these studies, factors intrinsic to the individual are correlated with depression levels. Predictors cited include a history of psychiatric illness prior to starting interferon treatment, 2,15,16 female sex, 17,18 lower age, 18 severity of disability, 17,19 and presence of depressive symptoms at baseline (measured at the start of the investigation). 19 Interferon use was not associated with depressive symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…Nous avons, quant à nous, utilisé un questionnaire standardisé [20] basé sur une des Cependant, les symptômes dépressifs sont un peu plus courants dans la SEP que dans la MP [13,21,39].…”
Section: Dépression Humeur Et Anxiétéunclassified